A systematic literature review on the challenges of teaching english in vocational high schools in Indonesia - Sugiarto, Dino; Widodo, Estu; Wicaksono, Bayu Hendro (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
In teaching English in vocational high schools, it is important to understand technical documents in English and use available technology to aid learning. However, various English teaching problems in vocational high schools in Indonesia still exist. Based on that background, this study will reveal teachers' and students' challenges in teaching English in vocational high schools. The researchers used a systematic literature review research design to gather the data accurately. However, the researchers selected the articles based on the exclusion and inclusion categories, following the Preferred Reporting Items for Systematic Reviews and meta-analysis methods. The findings stated that collaborative research was the most common approach in studying this topic, with ten studies conducted by multiple authors and only two conducted by individuals. The study also found that the case study method is the most commonly used for investigating the challenges of teaching English in vocational high schools, followed by descriptive qualitative research. Additionally, the analysis revealed a significant interest in the role of ICT in these challenges, as it is the third relevant word in the journals. In brief, 19 categories of challenges have been discovered from 12 articles. As the central part of the study, the results show that students’ motivation to learn English becomes the most apparent challenge faced by teachers in vocational high schools, followed by students’ language proficiency in the second position. Furthermore, the study found a close relationship between students' language proficiency and motivation, with highly motivated students achieving higher scores in English lessons. Other challenges identified in the survey include school facilities such as electricity, a language laboratory, an internet connection, and appropriate media or platforms to allow students to use English for communication and interaction.